Parametric Simulation and Exergy Analysis of a 30w Ethanol Fuel Cell: A Theoretical Approach - daniel C, Emeniru; Bright, Ogoro Zino; Ogbeifun E, Osazee; Fredrick T, Owutuamor; Adegboyega S., Olawale; John Enemona, Oguche (European Scientific Journal, ESJ, 2022)
Ethanol has the potential of being an abundant biofuel considering the raw materials and indigenous technology available. Due to its oxidation tendency, higher energy density, nontoxic and environmental affability, several studies have confirmed and emphasized ethanol’s choice and adaptability for usage in fuel cells. This paper aimed at parametric simulation and exergy analysis of a 30W ethanol fuel cell using a theoretical approach. The simulation considers 1atm and 65oC operating conditions while making empirically significant assumptions about layer thicknesses and other parameters. Fixed and standard parameters from the literature were applied in the mathematical expressions and models that described the energy, power generation, over-potentials, and the efficiencies inherent in the simulation. From the simulation, voltage loss due to transport contributed about 80% of the 0.1211 V while total over-potential culminated to the 3.633W irreversible power. The exergy analysis of the simulated 95% Direct Ethanol Fuel Cell (DEFC) gave 89% cell efficiency for the generation of 3,050 kJ energy, 33.80 W ideal power, and 30.28W useful power in a 90 seconds operation at a 1.1267V potential.